Construction of Genetic Linkage Maps From a Hybrid Family of Large Yellow Croaker (Larimichthys crocea) - Yu, Xinxiu; Joshi, Rajesh; Gjøen, Hans Magnus; Lv, Zhenming; Kent, Matthew (Frontiers in Genetics, 2022)
Consensus and sex-specific genetic linkage maps for large yellow croaker (Larimichthys crocea) were constructed using samples from an F1 family produced by crossing a Daiqu female and a Mindong male. A total of 20,147 single nucleotide polymorphisms (SNPs) by restriction site associated DNA sequencing were assigned to 24 linkage groups (LGs). The total length of the consensus map was 1757.4 centimorgan (cM) with an average marker interval of 0.09 cM. The total length of female and male linkage map was 1533.1 cM and 1279.2 cM, respectively. The average female-to-male map length ratio was 1.2 ± 0.23. Collapsed markers in the genetic maps were re-ordered according to their relative positions in the ASM435267v1 genome assembly to produce integrated genetic linkage maps with 9885 SNPs distributed across the 24 LGs. The recombination pattern of most LGs showed sigmoidal patterns of recombination, with higher recombination in the middle and suppressed recombination at both ends, which corresponds with the presence of sub-telocentric and acrocentric chromosomes in the species. The average recombination rate in the integrated female and male maps was respectively 3.55 cM/Mb and 3.05 cM/Mb. In most LGs, higher recombination rates were found in the integrated female map, compared to the male map, except in LG12, LG16, LG21, LG22, and LG24. Recombination rate profiles within each LG differed between the male and the female, with distinct regions indicating potential recombination hotspots. Separate quantitative trait loci (QTL) and association analyses for growth related traits in 6 months fish were performed, however, no significant QTL was detected. The study indicates that there may be genetic differences between the two strains, which may have implications for the application of DNA-information in the further breeding schemes.